International Humanitarian Law and Hybrid Warfare - Łubiński, Piotr (Taylor & Francis, 2026)
This groundbreaking monograph offers a comprehensive legal and conceptual analysis of hybrid warfare and hybrid threats—two evolving challenges that blur the boundaries between war and peace. Drawing from international law, political science, and security studies, the book explores how states and non-state actors exploit legal, informational, and cyber tools to undermine adversaries without crossing the threshold of conventional warfare. With in-depth case studies and a critical review of doctrines from NATO, the EU, China, and Russia, the author maps the conceptual thresholds that distinguish hybrid threats from hybrid warfare. The book introduces “hybrid legality” as a framework to understand how international humanitarian law, human rights law, and sovereignty norms are manipulated in modern conflicts. Emphasizing the risks of conceptual ambiguity, it warns against the overuse of terms like “hybrid war” and “hybrid attack,” which may lead to alarm fatigue and legal confusion. Instead, it argues for precision and interdisciplinary insight to confront these threats effectively. With a unique focus on legal thresholds and norms, the volume is essential reading for scholars, policymakers, and practitioners navigating today’s increasingly multipolar and legally ambiguous security environment.